Carbon emission accounting for power transmission and transformation equipment: An extended life cycle approach - Xiaomin Chen; Yangting Ou (Energy Reports, 2023)
After the Chinese government announced its goals of carbon peaking and carbon neutrality in September 2020, a series of carbon reduction policies have been introduced on the energy consumption and production side without taking into account energy transmission and distribution. To address this issue, this paper introduces a new approach to estimate carbon emissions by extending the life cycle approach. It then calculates the comprehensive life cycle costs, including economic and carbon costs. This approach not only serves as a basis for power companies to consider when planning transmission and transformation projects, but also provides a theoretical basis for the government to formulate carbon reduction policies in energy transmission and distribution. Taking one 220kV substation in Fujian Province as an example, the results reveal that the life cycle economic costs are 102.88644 million yuan, accounting for 97.30%, while the carbon costs are 2.85628 million yuan (the carbon trading price is taken as the average carbon trading price of 60.45 yuan/ton published by Shanghai Environment and Energy Exchange on 22 August 2022), accounting for 2.70%, and the comprehensive life cycle economic costs are 105.74272 million yuan.